Medical implement
Patent Information
- Application Number
- CN202580021971.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2024-03-28
- Filing Date
- 2025-03-07
- Publication Date
- 2026-10-30
Smart Images

Figure CN123022444A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to medical devices. Background Technology
[0002] For medical devices such as catheters and guidewires inserted into the body, excellent lubricity is required to reduce damage to blood vessels and other tissues and improve operator maneuverability. Therefore, medical devices with a lubricating hydrophilic polymer layer on the surface of the substrate have been developed and put into practical use. On the other hand, for such medical devices, it is also important to maintain the lubricating hydrophilic polymer layer on the substrate surface during operator use to ensure operability. Therefore, coatings formed from hydrophilic polymers require not only excellent lubricity but also durability against abrasion, scratching, and other loads.
[0003] From this perspective, Japanese Patent Application Publication No. 8-33704 (corresponding to US Patent No. 5670558) discloses a medical device in which a polymer solution is prepared by dissolving a water-soluble or water-swellable polymer in a solvent that swells the substrate of the medical device, the substrate of the medical device is immersed in the polymer solution to swell, and the polymer is further crosslinked or polymerized on the surface of the substrate layer to form a surface lubricating layer on the surface of the substrate layer.
[0004] According to the technology disclosed in the aforementioned documents, a surface lubricating layer that exhibits good lubricity can be fixed to a substrate. Summary of the Invention
[0005] The aforementioned literature discloses block copolymers, preferably comprising a hydrophilic portion exhibiting lubricity and an epoxy group portion, as water-soluble or water-swellable polymers. Furthermore, when using such block copolymers, the epoxy groups of the block copolymer can be crosslinked through a heating process to form a surface lubricating layer that is less prone to peeling.
[0006] On the other hand, in recent years, medical devices have seen significant miniaturization and reduction in diameter, leading to the widespread adoption of medical methods that deliver devices to narrow lesion sites by passing through highly tortuous biological lumens. Furthermore, with the increasing complexity of medical procedures, the operation of medical devices can sometimes last for longer periods. Therefore, even when treating lesion sites by passing through very complex biological lumens, techniques that further improve the lubricity and lubrication maintenance (durability) of the device surface are required compared to existing technologies in order to maintain good operability of the medical device for extended periods. More specifically, even when repeatedly sliding the medical device against the biological lumen wall to deliver it to the lesion site through complex biological lumens (e.g., when delivering the device to the lesion site through sections with small bending radii, sections with continuous bends in the biological lumen, or sections with narrow inner diameters of the biological lumen), techniques that further improve the lubricity and durability (especially sliding durability) of the device surface are required compared to existing technologies in order to maintain good operability of the medical device.
[0007] Therefore, there is a need for technologies that can further improve the lubricity and durability (especially sliding durability) of the surface lubricating layer of medical devices and support complex and sophisticated medical procedures.
[0008] The present invention was made in view of the above circumstances, and its object is to provide a medical device having a lubricating layer that further improves lubricity and durability (especially sliding durability).
[0009] The inventors of this application conducted in-depth research to solve the aforementioned problems. As a result, they discovered that by using a copolymer with a specific composition and specific structural units in the lubricating layer, the aforementioned problems could be solved, thus completing this invention.
[0010] That is, the above objective can be achieved by the following medical device, (1) a medical device having a substrate layer and a lubricating layer formed on at least a portion of the substrate layer, wherein the lubricating layer comprises a copolymer having: a structural unit (A) comprising a structural unit (A-1) derived from a hydrophilic monomer having an acrylamide group or a methacrylamide group, and a structural unit (A-2) derived from a hydrophilic monomer having at least one of a carboxyl group and a salt of a carboxyl group; and a structural unit (B) derived from a hydrophobic monomer having an epoxy group, wherein the content of the structural unit (A) is 10 moles or more and 90 moles or less relative to 1 mole of the structural unit (B), and the content of the structural unit (A-2) is 3 mol% or more and 40 mol% or less relative to the total amount of the structural unit (A-1) and the structural unit (A-2).
[0011] (2) In the medical device of (1) above, it is preferred that the content of the above structural unit (A) is 25 moles or more and 70 moles or less relative to 1 mole of the above structural unit (B).
[0012] (3) In the medical device of (1) or (2) above, it is preferred that the content of the above structural unit (A-2) is 6 mol% or more and 30 mol% or less relative to the total amount of the above structural unit (A-1) and the above structural unit (A-2).
[0013] (4) In any of the medical devices described in (1) to (3) above, preferably the above structural unit (A-1) is a structural unit derived from at least one monomer selected from the group consisting of acrylamide, N-methylacrylamide, N,N-dimethylacrylamide, N-ethylacrylamide, N,N-diethylacrylamide, N,N-dimethylaminopropylacrylamide, N,N-dimethylaminopropylmethylacrylamide, 2-acrylamido-2-methylpropanesulfonic acid, N-(2-hydroxyethyl)acrylamide, N-(2-hydroxypropyl)acrylamide and N-(2-hydroxybutyl)acrylamide.
[0014] (5) In any of the medical devices described in (1) to (4) above, the structural unit (A-2) is preferably a structural unit derived from at least one monomer selected from the group consisting of acrylic acid and methacrylic acid, as well as their alkali metal salts, alkaline earth metal salts and quaternary ammonium salts.
[0015] (6) In any of the medical devices described in (1) to (5) above, preferably the above structural unit (B) is a structural unit derived from at least one monomer selected from the group consisting of glycidyl acrylate, glycidyl methacrylate, 3,4-epoxycyclohexyl methyl acrylate, 3,4-epoxycyclohexyl methyl methacrylate, β-methyl glycidyl acrylate and β-methyl glycidyl methacrylate.
[0016] (7) In any of the medical devices described in (1) to (6) above, it is preferred that the above structural unit (A) is formed by randomly arranging the above structural units (A-1) and (A-2).
[0017] (8) In any of the medical devices described in (1) to (6) above, it is preferred that the above structural unit (B) is configured in a segmental manner.
[0018] (9) In any of the medical devices described in (1) to (6) above, it is preferred that the above structural unit (A) is composed of the above structural units (A-1) and (A-2) arranged randomly, and the above structural unit (B) is arranged in a segmental manner.
[0019] (10) The medical device in any of (1) to (9) above is preferably a catheter, stent or guidewire. Attached Figure Description
[0020] [ Figure 1 ] Figure 1 This is a graph showing the gel fraction of copolymers 6 and 12, and the sliding resistance values of sample 6 having a lubricating layer containing copolymer 6 and sample 12 having a lubricating layer containing copolymer 12 on the 20th time. Detailed Implementation
[0021] One aspect of the present invention relates to a medical device comprising a substrate layer and a lubricating layer formed on at least a portion of the substrate layer, wherein the lubricating layer comprises a copolymer having: a structural unit (A) comprising a structural unit (A-1) derived from a hydrophilic monomer having an acrylamide group or a methacrylamide group, and a structural unit (A-2) derived from a hydrophilic monomer having at least one of a carboxyl group and a salt of a carboxyl group; and a structural unit (B) derived from a hydrophobic monomer having an epoxy group, wherein the content of the structural unit (A) is 10 mol to 90 mol relative to 1 mol of the structural unit (B), and the content of the structural unit (A-2) is 3 mol% to 40 mol% relative to the total amount of the structural units (A-1) and (A-2). With this configuration, a medical device having a lubricating layer with further improved lubricity and durability (particularly sliding durability) can be provided.
[0022] In this specification, "hydrophilic monomer having an acrylamide group or a methacrylamide group" is also simply referred to as "hydrophilic monomer (A-1)" or "the hydrophilic monomer (A-1) of the present invention." "Structural unit (A-1) derived from a hydrophilic monomer having an acrylamide group or a methacrylamide group" is also simply referred to as "structural unit (A-1)" or "the structural unit (A-1) of the present invention." "Hydrophilic monomer having at least one of a carboxyl group and a carboxyl salt" is also simply referred to as "hydrophilic monomer (A-2)" or "the hydrophilic monomer (A-2) of the present invention." "At least one of a carboxyl group and a carboxyl salt" is also simply referred to as "carboxyl (salt)." "Structural unit (A-2) derived from a hydrophilic monomer having at least one of a carboxyl group and a carboxyl salt" is also simply referred to as "structural unit (A-2)" or "the structural unit (A-2) of the present invention." "Hydrophobic monomer having an epoxy group" is also simply referred to as "hydrophobic monomer" or "the hydrophobic monomer of the present invention." The term "structural unit (B) derived from a hydrophobic monomer having an epoxy group" is also simply referred to as "structural unit (B)" or "the structural unit (B) of the present invention". The term "copolymer having: structural unit (A) comprising a structural unit (A-1) derived from a hydrophilic monomer having an acrylamide group or a methacrylamide group, and a structural unit (A-2) derived from a hydrophilic monomer having at least one of a carboxyl group and a salt of a carboxyl group; and a structural unit (B) derived from a hydrophobic monomer having an epoxy group" is also simply referred to as "copolymer" or "the copolymer of the present invention".
[0023] In this specification, the range "X~Y" includes both X and Y, meaning "above X and below Y". In this specification, the term "(meth)acrylic" includes both acrylic acids and methacrylic acids. Therefore, for example, the term "(meth)acrylic acid" includes both acrylic acid and methacrylic acid. Similarly, the term "(meth)acrylate" includes both acrylates and methacrylates. Therefore, the term "(meth)acrylate glycidyl ester" includes both glycidyl acrylate and glycidyl methacrylate.
[0024] In this specification, when a structural unit is specified as "derived" from a monomer, it means that the structural unit is a structural unit generated by breaking the polymerizable unsaturated double bonds of the corresponding monomer.
[0025] Unless otherwise specified, the determination of operation and physical properties shall be carried out at room temperature (20-25°C) and relative humidity (40-60%RH).
[0026] <Medical Equipment> One aspect of the present invention relates to a medical device comprising a substrate layer and a lubricating layer formed on at least a portion of the substrate layer. The lubricating layer comprises a copolymer having: structural unit (A) comprising structural unit (A-1) derived from a hydrophilic monomer having an acrylamide group or a methacrylamide group, and structural unit (A-2) derived from a hydrophilic monomer having at least one of a carboxyl group and a salt of a carboxyl group; and structural unit (B) derived from a hydrophobic monomer having an epoxy group. The content of the structural unit (A) is 10 mol to 90 mol relative to 1 mol of the structural unit (B). The content of the structural unit (A-2) is 3 mol% to 40 mol% relative to the total amount of the structural units (A-1) and (A-2). The lubricating layer having the above configuration, because it contains structural unit (A-2) in a ratio of 3 mol% to 40 mol% relative to the total amount of the structural units (A-1) and (A-2), can improve lubricity (smoothness). Furthermore, in the lubricating layer having the above-described configuration, since the structural unit (A) comprises structural unit (A-2) in a proportion of 3 mol% to 40 mol% relative to the total amount of structural unit (A-1) and structural unit (A-2), and the copolymer comprises 10 mol to 90 mol of structural unit (A) relative to 1 mol of structural unit (B), it can exhibit excellent lubricity (smoothness) and durability (especially sliding durability). Therefore, the medical device having the above-described configuration can exhibit excellent lubricity and lubrication maintenance (sliding durability) even when repeatedly sliding against the wall of a biological lumen in order to deliver the medical device to the lesion site through a complex biological lumen (for example, when delivering the medical device to the lesion site through a portion of the biological lumen with a small radius of curvature, a portion of the biological lumen with continuous bends, or a portion of the biological lumen with a narrow inner diameter). Therefore, according to the present invention, it is possible to provide a medical device having a lubricating layer with further improved lubricity and durability (especially sliding durability).
[0027] The preferred embodiments of the present invention will be described below. It should be noted that the present invention is not limited to the following embodiments, and various modifications can be made within the scope of the claims. Furthermore, the embodiments described in this specification can be combined in any way to form other embodiments.
[0028] Throughout this specification, unless otherwise specified, singular expressions should be understood to include the concept of their plural forms. Therefore, unless otherwise specified, articles in the singular form (e.g., "a," "an," "the," etc. in the English context) should be understood to include the concept of their plural forms. Furthermore, unless otherwise specified, the terminology used in this specification should be understood to be used in the meaning commonly understood in the art. Therefore, unless otherwise defined, all technical and technical terms used in this specification have the same meaning as commonly understood by those skilled in the art to which this invention pertains. In cases of conflict, this specification (including definitions) takes precedence.
[0029] [Substrate Layer (Substrate)] The substrate layer (substrate) used in this invention can be made of any material, which can be appropriately selected according to the application. Specifically, the materials constituting (forming) the substrate layer include metallic materials, polymeric materials, ceramics, etc. Here, the substrate layer may be wholly (entirely) composed of any of the above-mentioned materials, or it may have a structure in which the surface of the core of the substrate layer composed of any of the above-mentioned materials is coated (coated) with other of the above-mentioned materials in an appropriate manner to form a substrate surface layer. Examples of the latter include: coating a metal material onto the surface of a substrate core made of a resin material or similar material using a suitable method (plating, metal evaporation, sputtering, or other conventionally known methods), thereby forming a substrate surface layer; coating a polymer material softer than the reinforcing material such as a metal material onto the surface of a substrate core made of a hard reinforcing material such as a metal or ceramic material using a suitable method (impregnation, spraying, coating, printing, or other conventionally known methods); or combining the reinforcing material of the substrate core with the polymer material of the substrate surface layer (through appropriate reaction treatment), thereby forming a substrate surface layer. The substrate core can also be a multilayer structure formed by stacking multiple layers of different materials, or a structure (composite) formed by connecting components of different materials together in a medical device. Furthermore, other intermediate layers can be further formed between the substrate core and the substrate surface layer. In addition, the surface layer of the substrate can also be a multilayer structure formed by stacking different materials, or a structure (composite) formed by connecting the various parts of a medical device made of different materials.
[0030] Among the materials constituting (forming) the aforementioned substrate layer, there are no particular restrictions on the metallic materials used; commonly used metallic materials for medical devices such as catheters, stents, and guidewires can be employed. Specifically, examples include various stainless steels (SUS) such as SUS304, SUS316, SUS316L, SUS420J2, and SUS630, as well as gold, platinum, silver, copper, nickel, cobalt, titanium, iron, aluminum, tin, or various alloys such as nickel-titanium (Ni-Ti) alloys, nickel-cobalt (Ni-Co) alloys, cobalt-chromium (Co-Cr) alloys, and zinc-tungsten (Zn-W) alloys. One or more of these materials can be used individually. The most suitable metallic material for the intended use as the substrate layer for catheters, stents, guidewires, etc., should be selected from the aforementioned metallic materials.
[0031] In addition, there are no particular restrictions on the materials used to form the above-mentioned substrate layer, and polymeric materials (resin materials or elastomer materials) can be used, such as those commonly used in medical devices such as catheters, stents, and guidewires. Specifically, examples include polyamide resin (nylon), linear low-density polyethylene (LLDPE), low-density polyethylene (LDPE), high-density polyethylene (HDPE), modified polyethylene and other polyethylene resins, polyolefin resins such as polypropylene resin, modified polyolefin resins, cyclic polyolefin resins, epoxy resins, polyurethane resins, diallyl phthalate resin (allyl resin), polycarbonate resins, polytetrafluoroethylene (PTFE), ethylene-tetrafluoroethylene (ETFE) and other fluororesins, amino resins (urea-formaldehyde resin, melamine resin, benzoguanamine resin), polyethylene terephthalate resin, polybutylene terephthalate resin and other polyester resins, polystyrene and other styrene resins, acrylic resins, polyacetal resins, vinyl acetate resins, phenolic resins, vinyl chloride resin (polyvinyl chloride (PVC)), silicone resins (silicone resins), polyether ether ketone (PEEK) and other polyimide resins, etc. In addition, thermoplastic elastomers such as polyurethane elastomers, polyester elastomers, and polyamide elastomers (nylon elastomers) can also be used as substrate materials. They can be used individually or in combination of two or more. Among the aforementioned polymer materials, the most suitable polymer material should be selected for the substrate layer of the catheter, stent, guidewire, etc., intended for use.
[0032] In addition, there are no particular restrictions on the shape of the above-mentioned substrate layer. It can be appropriately selected as sheet-like, wire-like, tubular, etc., depending on the application.
[0033] [Lubricating layer] A lubricating layer is formed (supported) on at least a portion of the aforementioned substrate layer (substrate). The reason for forming (supporting) the lubricating layer on at least a portion of the surface of the substrate layer is that, in medical devices such as catheters, stents, and guidewires intended for use, it is not necessary for the entire surface of these medical devices to be lubricated when wet; only the surface portion (sometimes a portion, sometimes all) where lubrication when wet is required is supported by the lubricating layer. Therefore, the lubricating layer includes the following forms: a form that is formed entirely covering only one side of the substrate layer; a form that is formed entirely covering both sides of the substrate layer; a form that is formed by covering portions of both sides of the substrate layer in the same or different forms; a form that is formed partially covering one side of the substrate layer, etc.
[0034] The lubricating layer comprises a copolymer having: a structural unit (A) comprising a structural unit (A-1) derived from a hydrophilic monomer having an acrylamide group or a methacrylamide group, and a structural unit (A-2) derived from a hydrophilic monomer having at least one of a carboxyl group and a salt of a carboxyl group; and a structural unit (B) derived from a hydrophobic monomer having an epoxy group.
[0035] The structural unit (A-1) comprising the structural unit (A) is derived from a hydrophilic monomer (A-1) having an acrylamide group (represented by the formula: H2=CH-C(=O)-N=) or a methacrylamide group (represented by the formula: CH2=C(CH3)-C(=O)-N=). This hydrophilic monomer exhibits swelling properties upon contact with bodily fluids (e.g., blood, urine) and aqueous solvents, thus imparting smoothness (lubricity) to the lubricating layer. Therefore, by introducing such a hydrophilic monomer-derived structural unit into the copolymer, the lubricating layer formed using this copolymer exhibits excellent smoothness (lubricity), reducing friction when medical devices come into contact with luminal walls such as blood vessel walls.
[0036] As a hydrophilic monomer (A-1), any monomer can be present as long as it has an acrylamide or methacrylamide group and exhibits lubricity in bodily fluids and aqueous solvents. Examples of such hydrophilic monomers (A-1) include acrylamide, methacrylamide, N-methylacrylamide, N-methylmethacrylamide, N,N-dimethylacrylamide, N,N-dimethylmethacrylamide, N-ethylacrylamide, N-ethylmethacrylamide, N,N-diethylacrylamide, N,N-diethylmethacrylamide, N,N-dimethylaminopropylacrylamide, N,N-dimethylaminopropylmethacrylamide, N,N-dimethylaminoethyl acrylate, N,N-dimethylaminoethyl methacrylate, 2-acrylamido-2-methylpropanesulfonic acid, N-(2-hydroxyethyl)acrylamide, N-(2-hydroxypropyl)acrylamide, and N-(2-hydroxybutyl)acrylamide. From the viewpoint of further imparting lubricity and ease of synthesis, the hydrophilic monomer (A-1) preferably comprises at least one selected from the group consisting of acrylamide, N-methylacrylamide, N,N-dimethylacrylamide, N-ethylacrylamide, N,N-diethylacrylamide, N,N-dimethylaminopropylacrylamide, N,N-dimethylaminopropylmethylacrylamide, 2-acrylamido-2-methylpropanesulfonic acid, N-(2-hydroxyethyl)acrylamide, N-(2-hydroxypropyl)acrylamide, and N-(2-hydroxybutyl)acrylamide. More preferably, it comprises at least one selected from the group consisting of acrylamide, N,N-dimethylacrylamide, and N,N-diethylacrylamide. Further preferably, it comprises acrylamide or N,N-dimethylacrylamide, and particularly preferably, it comprises N,N-dimethylacrylamide. The structural unit (A-1) derived from the hydrophilic monomer may be composed of only one hydrophilic monomer (A-1), or it may be composed of two or more hydrophilic monomers (A-1).
[0037] Specifically, in one embodiment of the present invention, the structural unit (A-1) derived from the hydrophilic monomer is a structural unit derived from at least one monomer selected from the group consisting of acrylamide, N-methylacrylamide, N,N-dimethylacrylamide, N-ethylacrylamide, N,N-diethylacrylamide, N,N-dimethylaminopropylacrylamide, N,N-dimethylaminopropylmethylacrylamide, 2-acrylamido-2-methylpropanesulfonic acid, N-(2-hydroxyethyl)acrylamide, N-(2-hydroxypropyl)acrylamide, and N-(2-hydroxybutyl)acrylamide. In one embodiment of the present invention, the structural unit (A-1) derived from the hydrophilic monomer is a structural unit derived from at least one monomer selected from the group consisting of acrylamide, N,N-dimethylacrylamide, and N,N-diethylacrylamide. In one embodiment of the present invention, the structural unit (A-1) derived from the hydrophilic monomer is derived from acrylamide or N,N-dimethylacrylamide. In one embodiment of the present invention, the structural unit (A-1) derived from the hydrophilic monomer is derived from N,N-dimethylacrylamide.
[0038] In addition to the structural unit (A-1) described above, structural unit (A-2) also comprises a hydrophilic monomer (hydrophilic monomer (A-2)) derived from at least one of a carboxyl group (-COOH) and a salt containing a carboxyl group. Structural unit (A-2) may also be composed of structural units derived from a hydrophilic monomer containing a carboxyl group and structural units derived from a hydrophilic monomer containing a salt containing a carboxyl group. Furthermore, the number (total) of carboxyl groups and carboxyl salts present in one hydrophilic monomer (A-2) is preferably 1 or 2, more preferably 1.
[0039] The effects of adding structural unit (A-2) to structural unit (A) are explained in detail below.
[0040] The epoxy groups present in structural unit (B) interact with other structural units (B) within the copolymer or with structural units (B) in adjacent copolymers during heat treatment, forming intermolecular crosslinking points and thus forming a lubricating layer. However, when the proportion of structural unit (B) in the overall copolymer is small (especially when the content of structural unit (B) is less than 5 mol% relative to all structural units constituting the copolymer), the proportion of other structural units (B) around the epoxy groups present in structural unit (B) decreases, and the rate of intermolecular crosslinking point formation between epoxy groups and other structural units (B) decreases. Therefore, when the proportion of structural unit (B) in the overall copolymer is small (especially when the content of structural unit (B) is less than 5 mol% relative to all structural units constituting the copolymer), there is room for improving the durability of the lubricating layer by increasing the number of epoxy groups that contribute to the formation of crosslinking points. Furthermore, when increasing the proportion of structural unit (B) in the overall copolymer to improve the durability of the lubricating layer (especially when the content of structural unit (B) is greater than 5 mol% relative to all structural units constituting the copolymer), the smoothness of the lubricating layer decreases as the proportion of structural unit (B) increases. Therefore, even in such cases, there is room to maintain the durability of the lubricating layer and improve its lubricity by increasing the swelling property of structural unit (A).
[0041] The copolymer of the present invention is designed with structural unit (A) having structural unit (A-1) and structural unit (A-2). Structural unit (A-2) is hydrophilic and has carboxyl groups (salts). The carboxyl groups (salts) present in structural unit (A-2) act as catalysts through heat treatment, causing ring-opening of the epoxy groups present in structural unit (B), thereby promoting chemical cross-linking between epoxy groups and between epoxy groups and carboxyl groups (salts). Therefore, a portion of the carboxyl groups (salts) present in structural unit (A-2) can promote chemical cross-linking between epoxy groups and between epoxy groups and carboxyl groups (salts) in the lubricating layer, thus improving the durability of the lubricating layer. In addition, even when no chemical bonds are formed between the carboxyl groups (salts) and epoxy groups, structural unit (A-2), as a hydrophilic material, contributes to the lubricity (swellability) of the lubricating layer. Therefore, the lubricating layer containing the copolymer of the present invention can further improve lubricity and durability (especially sliding durability) due to the presence of structural unit (A-2).
[0042] Furthermore, in the copolymer, structural unit (A) contributes to lubricity, while structural unit (B) contributes to durability. Therefore, the lubricity and durability of the copolymer are mutually restrictive. Consequently, it has been difficult to maintain durability and improve lubricity by adjusting the ratio of structural units (A) to structural units (B) in the copolymer in the past.
[0043] The copolymer of the present invention is configured such that structural unit (A) includes structural unit (A-2), which is hydrophilic and has carboxyl groups (salts). Therefore, even when increasing the composition ratio of structural unit (A) to improve lubricity, the copolymer of the present invention can promote the chemical crosslinking of epoxy groups present in structural unit (B) through the carboxyl groups (salts) present in structural unit (A-2), thereby improving the durability of the lubricating layer. Therefore, the lubricating layer containing the copolymer of the present invention can maintain durability (particularly sliding durability) and further improve lubricity due to the presence of structural unit (A-2).
[0044] It should be noted that the above content is speculative and the present invention is not limited thereto.
[0045] The hydrophilic monomer (A-2) can be any monomer as long as it is hydrophilic and has a carboxyl group (salt). Examples of such hydrophilic monomers (A-2) include acrylic acid, methacrylic acid, maleic anhydride, aspartic acid, glutamic acid, polyalginic acid, adipic acid, glutaric acid, and hyaluronic acid; as well as their alkali metal salts, alkaline earth metal salts, and quaternary ammonium salts (preferably NH4). + )wait.
[0046] From the viewpoint of improving the water absorption of structural unit (A-2), the salt of the carboxyl group is preferably an alkali metal salt, alkaline earth metal salt, or quaternary ammonium salt (preferably NH4). + Examples of alkali metal salts include lithium, potassium, and sodium salts with carboxyl groups. Examples of alkaline earth metal salts include magnesium, calcium, strontium, and barium salts. It should be noted that in the case of alkaline earth metal salts where the hydrophilic monomer (A-2) has a carboxyl group, the alkaline earth metal salt bonds to one molecule of the hydrophilic monomer (A-2) or two adjacent carboxyl groups within two different hydrophilic monomers (A-2) (forming -C(=O)-OXOC(=O)-(X=alkaline earth metal salt)). The structural unit (A-2) derived from the hydrophilic monomer can consist of only one type of hydrophilic monomer (A-2), or it can consist of two or more types of hydrophilic monomers (A-2).
[0047] The hydrophilic monomer (A-2) is preferably selected from acrylic acid and methacrylic acid; and their alkali metal salts, alkaline earth metal salts and quaternary ammonium salts (preferably NH4). +The aforementioned hydrophilic monomer (A-2) exhibits excellent water absorption and functions as an acid that opens the ring of the epoxy group present in the catalytic structural unit (B). Therefore, the copolymer of the present invention, due to the presence of the structural unit (A-2) derived from the hydrophilic monomer, can improve the swelling properties of the lubricating layer and further increase the number of epoxy groups (ring-opening epoxy groups) on the lubricating layer that contribute to the crosslinking reaction. Therefore, a lubricating layer comprising the copolymer having the aforementioned structural unit (A-2) derived from the hydrophilic monomer can improve lubricity and exhibit higher film strength (crosslinking density), further improving durability.
[0048] The hydrophilic monomer (A-2) is more preferably acrylic acid or an alkali metal salt thereof. As described above, the carboxyl group of the structural unit derived from acrylic acid or the structural unit derived from the alkali metal salt of acrylic acid can catalyze the ring-opening of the epoxy groups present in the structural unit (B), promoting the chemical cross-linking of epoxy groups with each other and the chemical cross-linking of carboxyl groups with epoxy groups. Therefore, the structural unit derived from acrylic acid or the structural unit derived from the alkali metal salt of acrylic acid can increase the number of epoxy groups of the copolymer that contribute to the cross-linking reaction on the lubricating layer, and can further improve the film strength (cross-linking density) (and thus durability) of the lubricating layer.
[0049] Furthermore, copolymers having acrylic acid-derived structural units or sodium acrylate-derived structural units that do not form chemical crosslinks with the epoxy groups present in structural unit (B) are hydrophilic and have excellent water absorption. Therefore, copolymers having acrylic acid-derived or sodium acrylate-derived structural units exhibit swelling properties upon contact with bodily fluids (e.g., blood, urine) and aqueous solvents, imparting superior smoothness (lubricity) to the lubricating layer. Thus, when the copolymer has acrylic acid-derived structural units or alkali metal salt-derived structural units as structural units (A-2), the lubricating layer formed using this copolymer exhibits superior smoothness (lubricity), further reducing friction when medical devices contact the walls of lumens such as blood vessels.
[0050] Therefore, the lubricating layer comprising the copolymers involved in this invention can further improve excellent lubricity and durability (especially sliding durability).
[0051] Specifically, in one embodiment of the present invention, structural unit (A-2) is a structural unit derived from at least one monomer selected from the group consisting of acrylic acid and methacrylic acid, and their alkali metal salts, alkaline earth metal salts, and quaternary ammonium salts. In one embodiment of the present invention, structural unit (A-2) is a structural unit derived from at least one monomer selected from the group consisting of acrylic acid and alkali metal salts of acrylic acid. In one embodiment of the present invention, structural unit (A-2) has at least one of a structural unit derived from acrylic acid and a structural unit derived from sodium acrylate.
[0052] It should be noted that when the structural unit (A-2) comprises a structural unit derived from a hydrophilic monomer having a carboxyl group and a structural unit derived from a hydrophilic monomer having a carboxyl group salt, the proportion (hereinafter also referred to as "substitution rate") (mol%) of the structural unit derived from the hydrophilic monomer having a carboxyl group salt in the entire structural unit (A-2) is preferably 20 mol% or more and 100 mol% or less, more preferably 50 mol% or more and 80 mol% or less.
[0053] Structural unit (A) has structural unit (A-1) and structural unit (A-2). Here, structural unit (A-1) and structural unit (A-2) are preferably arranged randomly (structural unit (A-1) and structural unit (A-2) constitute a random copolymer). Thus, the carboxyl groups (salts) present in structural unit (A-2) are dispersed within the chain segments of structural unit (A). Therefore, the carboxyl groups (salts) present in structural unit (A-2) readily form chemical crosslinks with the epoxy groups present in structural unit (B) at various sites of structural unit (A). Therefore, the film strength (crosslink density) of the lubricating layer is increased, and durability can be further improved. That is, in one embodiment of the present invention, structural unit (A) is configured such that the aforementioned structural units (A-1) and the aforementioned structural unit (A-2) are arranged randomly.
[0054] It should be noted that "structural unit (A-1) and structural unit (A-2) constitute a random copolymer" means that the hydrophilic monomer (A-1) constituting structural unit (A-1) and the hydrophilic monomer (A-2) constituting structural unit (A-2) constitute a random copolymer. For example, if structural unit (A-1) is composed of one type of hydrophilic monomer (A-1) and structural unit (A-2) is composed of one type of hydrophilic monomer (A-2), it means that these two hydrophilic monomers constitute a random copolymer. Conversely, if structural unit (A-1) is composed of two types of hydrophilic monomers (A-1) and structural unit (A-2) is composed of one type of hydrophilic monomer (A-2), it means that these three hydrophilic monomers constitute a random copolymer. In addition, when structural unit (A-1) is composed of one hydrophilic monomer (A-1) and structural unit (A-2) is composed of two hydrophilic monomers (A-2), it means that the three hydrophilic monomers constitute a random copolymer.
[0055] Structural unit (A) comprises structural units (A-1) and (A-2). The ratio of structural unit (A-1) to structural unit (A-2) is such that the content of structural unit (A-2) relative to the total amount of structural units (A-1) and (A-2) is between 3 mol% and 40 mol%. When the content of structural unit (A-2) relative to the total amount of structural units (A-1) and (A-2) is less than 3 mol%, the composition of structural unit (A-2) is too small, and the amount of carboxyl groups (salts) of the hydrophilic monomer (A-2) participating in the chemical crosslinking with the epoxy groups present in structural unit (B) is insufficient. Therefore, although the lubricating layer exhibits excellent lubricity, its durability (crosslinking density) is poor. On the other hand, when the content of structural unit (A-2) relative to the total amount of structural units (A-1) and (A-2) is greater than 40 mol%, the polymerization reactant yellows, and a polymer suitable for use in the lubricating layer cannot be obtained. From the perspective of balancing lubricity and durability (crosslinking density) and manufacturing operability, the content of structural unit (A-2) is preferably 6 mol% or more and 30 mol% or less relative to the total amount of structural unit (A-1) and structural unit (A-2), and the content of structural unit (A-2) is preferably 6.5 mol% or more and 20.0 mol% or less relative to the total amount of structural unit (A-1) and structural unit (A-2).
[0056] In addition to having structural unit (A), the copolymers involved in this invention also have structural units (B) derived from hydrophobic monomers having epoxy groups.
[0057] Structural unit (B) is derived from a hydrophobic monomer with an epoxy group. The hydrophobic monomer with an epoxy group has an epoxy group as a reactive group. During heat treatment, the epoxy groups present in structural unit (B) interact with other structural units (B) within the copolymer or with structural units (B) in adjacent copolymers, forming intermolecular crosslinking points. Furthermore, the epoxy groups present in structural unit (B) can also form chemical crosslinks with other epoxy groups or carboxyl groups (salts) through ring-opening via heat treatment using carboxyl groups (salts) within the copolymer or with carboxyl groups (salts) in adjacent copolymers as catalysts. Therefore, the film strength and durability of the lubricating layer are improved. Additionally, if the surface of the substrate layer has functional groups capable of reacting with epoxy groups, the epoxy groups present in structural unit (B) can also form crosslinked structures with these functional groups in the substrate layer, further improving the durability of the lubricating layer.
[0058] The hydrophobic monomer constituting the copolymer can be any compound that has an epoxy group, without particular limitation, and can be any known compound. From the perspective of ease of crosslinking and easy control of polymerization, the hydrophobic monomer having an epoxy group preferably includes at least one selected from the group consisting of glycidyl acrylate, glycidyl methacrylate (GMA), 3,4-epoxycyclohexyl acrylate, 3,4-epoxycyclohexyl methacrylate, β-methyl glycidyl acrylate, and β-methyl glycidyl methacrylate. Glycidyl acrylate is more preferred, and particularly preferred, considering its ability to further promote crosslinking reaction and ease of manufacture. The structural unit (B) derived from the hydrophobic monomer can be composed of only one hydrophobic monomer, or it can be composed of two or more hydrophobic monomers.
[0059] That is, in one embodiment of the present invention, structural unit (B) is a structural unit derived from at least one monomer selected from the group consisting of glycidyl acrylate, glycidyl methacrylate, 3,4-epoxycyclohexyl methyl acrylate, 3,4-epoxycyclohexyl methyl methacrylate, β-methyl glycidyl acrylate, and β-methyl glycidyl methacrylate. In one embodiment of the present invention, structural unit (B) is a structural unit derived from glycidyl acrylate or glycidyl methacrylate. In one embodiment of the present invention, structural unit (B) is a structural unit derived from glycidyl methacrylate.
[0060] The copolymer has structural units (A) and structural units (B). Here, in the copolymer, structural units (A) and (B) can be arranged randomly, or they can be arranged in a block configuration. Preferably, the copolymer has structural units (A) and (B) arranged in a block configuration. That is, the copolymer is preferably a block copolymer, which is obtained by covalently linking the ends of the copolymer composed of structural units (A) to the ends of the polymer of structural units (B), thus connecting blocks composed of structural units (A) with blocks composed of structural units (B). If it is a block copolymer, better results can be obtained in terms of film strength (crosslinking density) and lubricity of the lubricating layer.
[0061] Here, in the "segment composed of structural unit (A)," structural unit (A-1) and structural unit (A-2) can be arranged randomly, or structural unit (A-1) and structural unit (A-2) can also be arranged in a segmental manner. Among them, as mentioned above, in the "segment composed of structural unit (A)," it is preferable that structural unit (A-1) and structural unit (A-2) are arranged randomly.
[0062] It should be noted that "the random arrangement of structural units (A) and (B)" refers to the random copolymer formed by the hydrophilic monomer (A-1) constituting structural unit (A), the hydrophilic monomer (A-2) constituting structural unit (A), and the hydrophobic monomer constituting structural unit (B).
[0063] That is, in one embodiment of the present invention, the structural unit (B) is configured in a segmented manner. In another embodiment of the present invention, the structural unit (A) is configured in a random manner with the aforementioned structural units (A-1) and (A-2), and the structural unit (B) is configured in a segmented manner.
[0064] In this specification, "block configuration of structural unit (B)" means that blocks consisting only of structural unit (B) exist in the main chain of the copolymer, i.e., -[structural unit (B)] n [- (n is an integer greater than or equal to 2) exists in the main chain of the copolymer. It should be noted that in this morphology, when the structural unit (B) is composed of two or more hydrophobic monomers, these two or more hydrophobic monomers exist within one block. For example, when the structural unit (B) is composed of two different structural units (Y-1) and structural unit (Y-2), -[structural unit (Y-1)] m1 -Structural unit (Y-2) m2 ] m- (m1 and m2 are each an integer greater than 1, m is an integer greater than 2, and structural units (Y-1) and (Y-2) can be arranged in a block-like or random configuration) exist in the main chain of the copolymer.
[0065] The copolymer has: structural unit (A) having structural units (A-1) and (A-2); and structural unit (B). The content of structural unit (A) is more than 10 moles and less than 90 moles of structural unit (B) per mole. When the content of structural unit (A) is less than 10 moles of structural unit (B) per mole, the composition of structural unit (A) derived from hydrophilic monomers is too small, resulting in poor lubricity (smoothness, swelling rate) of the lubricating layer. When the content of structural unit (A) is greater than 90 moles of structural unit (B) per mole, the composition of structural unit (B) derived from hydrophobic monomers is too small, the lubricating layer cannot exhibit sufficient film strength (crosslinking density), and the durability is poor. From the viewpoint of achieving a better balance between durability (crosslinking density) and lubricity (smoothness, swelling rate), the content of structural unit (A) is preferably 25 moles or more and 70 moles or less relative to 1 mole of structural unit (B), and more preferably 30 moles or more and 60 moles or less relative to 1 mole of structural unit (B).
[0066] The content (composition) of structural unit (B) relative to all structural units constituting the copolymer is preferably 0.8 mol% or more, more preferably 1 mol% or more, and particularly preferably 1.5 mol% or more. Furthermore, the content (composition) of structural unit (B) relative to all structural units constituting the copolymer is preferably 13 mol% or less, more preferably 10 mol% or less, further preferably 5 mol% or less, and particularly preferably 3.0 mol% or less. In one embodiment of the present invention, the content (composition) of structural unit (B) relative to all structural units constituting the copolymer is 0.8 mol% or more and 13 mol% or less. In one embodiment of the present invention, the content (composition) of structural unit (B) relative to all structural units constituting the copolymer is 1 mol% or more and 10 mol% or less. In one embodiment of the present invention, the content (composition) of structural unit (B) relative to all structural units constituting the copolymer is 1 mol% or more and 5 mol% or less. In one embodiment of the present invention, the content (composition) of structural unit (B) relative to all structural units constituting the copolymer is 1.5 mol% or more and 3.0 mol% or less. If it falls within this range, the lubricating layer exhibits sufficient film strength (crosslink density) and can provide excellent durability.
[0067] (Other structural units) The copolymers involved in this invention must contain structural units (A) and (B), but may also contain other structural units in addition to these structural units. In the case where the copolymer has other structural units, examples of monomers constituting other structural units (other monomers) include 4-hydroxybutyl methacrylate, 2-hydroxypropyl methacrylate, 2-hydroxybutyl methacrylate, 6-hydroxyhexyl methacrylate, 1,4-cyclohexanediol mono(meth)acrylate, 1-chloro-2-hydroxypropyl methacrylate, diethylene glycol mono(meth)acrylate, 1,6-hexanediol mono(meth)acrylate, pentaerythritol tri(meth)acrylate, dipentaerythritol penta(meth)acrylate, neopentyl glycol mono(meth)acrylate, trimethylolpropane di(meth)acrylate, trimethylolethane di(meth)acrylate, 2-hydroxy-3-phenyloxypropyl methacrylate, 4-hydroxycyclohexyl methacrylate, 2-hydroxy-3-phenyloxy methacrylate, triethylene glycol, tripropylene glycol, etc. Other structural units may consist of only one other type of monomer, or they may consist of two or more other types of monomers.
[0068] In cases where the copolymers involved in this invention have other structural units, the copolymers involved in this invention are preferably substantially composed of structural units (A) and (B) (the content of other structural units is greater than 0 mol% and less than 5 mol%). In this configuration, the copolymers involved in this invention can achieve a good balance between the lubricity (surface lubricity) provided by the structural unit (A) derived from the hydrophilic monomer and the durability provided by the structural unit (B) derived from the hydrophobic monomer having an epoxy group. More preferably, the copolymers involved in this invention (preferably block copolymers of structural units (A) and (B)) are composed only of structural units (A) and (B) (the content of other structural units is 0 mol%).
[0069] It should be noted that the copolymer having the above composition can be controlled by adjusting the charging ratio (molar ratio) of each monomer to the range described above. Therefore, the charging ratio (molar ratio) of the hydrophilic monomer to the hydrophobic monomer during the copolymer manufacturing stage is preferably within the range described above.
[0070] The composition (molar ratio) of the structural units of the copolymer can be determined, for example, by NMR analysis of the copolymer. 1 H-NMR measurement, 13 This can be confirmed by methods such as C-NMR determination. For example, the composition of each structural unit can be determined by measuring the copolymer solution. 1 The composition (molar ratio) of each structural unit can be determined by the integral ratio of the signal intensities of the H-NMR spectrum. Similarly, the composition of each structural unit can be determined by measuring the copolymer solution... 13The composition (molar ratio) of each structural unit is determined by the integral ratio of the signal intensities of each C-NMR spectrum.
[0071] In one embodiment of the invention, the copolymer involved in the invention is substantially composed of: a structural unit (A-1) derived only from at least one monomer selected from the group consisting of acrylamide, N-methylacrylamide, N,N-dimethylacrylamide, N-ethylacrylamide, N,N-diethylacrylamide, N,N-dimethylaminopropylacrylamide, N,N-dimethylaminopropylmethylacrylamide, 2-acrylamido-2-methylpropanesulfonic acid, N-(2-hydroxyethyl)acrylamide, N-(2-hydroxypropyl)acrylamide and N-(2-hydroxybutyl)acrylamide, and derived from... The structural unit (A) is composed of a structural unit (A-2) of at least one monomer selected from the group consisting of acrylic acid and methacrylic acid, and their alkali metal salts, alkaline earth metal salts and quaternary ammonium salts; and a structural unit (B) is composed of a structural unit derived from at least one monomer selected from the group consisting of glycidyl acrylate, glycidyl methacrylate, 3,4-epoxycyclohexyl acrylate, 3,4-epoxycyclohexyl methacrylate, β-methyl glycidyl acrylate and β-methyl glycidyl methacrylate, or is composed only of the above structural unit (A) and the above structural unit (B). In one embodiment of the present invention, the copolymer involved in the present invention is substantially composed of: structural units (A) consisting only of structural units (A-1) derived from at least one monomer selected from the group consisting of acrylamide, N,N-dimethylacrylamide and N,N-diethylacrylamide, and structural units (A-2) derived from at least one monomer selected from the group consisting of acrylic acid and alkali metal salts of acrylic acid; and structural units (B) derived from glycidyl acrylate or glycidyl methacrylate, or consisting only of the above structural units (A) and the above structural units (B). In one embodiment of the present invention, the copolymer involved in the present invention is substantially composed of: structural units (A) consisting only of structural units (A-1) derived from acrylamide or N,N-dimethylacrylamide, and structural units (A-2) derived from at least one monomer selected from the group consisting of acrylic acid and alkali metal salts of acrylic acid; and structural units (B) derived from glycidyl acrylate or glycidyl methacrylate, or consisting only of the above structural units (A) and the above structural units (B).
[0072] From the perspective of solubility, the weight-average molecular weight of the copolymer involved in this invention is preferably 10,000 to 10,000,000. From the perspective of ease of preparation of the coating solution, the weight-average molecular weight of the copolymer is more preferably 100,000 to 5,000,000. In this specification, "weight-average molecular weight" is a value determined by gel permeation chromatography (GPC) using polystyrene as a standard.
[0073] The thickness of the lubricating layer (dry film thickness) is, for example, 0.1 to 10 μm, preferably 0.5 to 5 μm, and more preferably about 1 to 3 μm.
[0074] There are no particular limitations on the manufacturing method of the copolymers involved in this invention, and known methods can be applied in the same way or with appropriate modifications. For example, when the copolymer involved in this invention is a block copolymer of structural unit (A) and structural unit (B), conventionally known polymerization methods such as living radical polymerization, polymerization using macromolecular initiators, and polycondensation can be used to produce it. Among these, considering the ease of controlling the molecular weight and molecular weight distribution of structural units (sites) derived from hydrophobic monomers and structural units (sites) derived from hydrophilic monomers, living radical polymerization or polymerization using macromolecular initiators is preferred. As for living radical polymerization, there are no particular limitations, and methods described in Japanese Patent Application Publication No. 11-263819, Japanese Patent Application Publication No. 2002-145971, and Japanese Patent Application Publication No. 2006-316169, as well as atom transfer radical polymerization (ATRP), can be applied in the same way or with appropriate modifications. In addition, in polymerization methods using macromolecular initiators, for example, after preparing a macromolecular initiator containing free radical polymerizable groups such as hydrophobic monomers with epoxy groups and peroxide groups, block copolymers having structural units (A) and structural units (B) (and structural units derived from other monomers as needed) can be produced by polymerizing the macromolecular initiator, hydrophilic monomers (A-1) and (A-2), and other monomers as needed, in a polymerization solvent.
[0075] In the above polymerization, the mixing ratio of the hydrophilic monomer (A-1), the hydrophilic monomer (A-2), and the hydrophobic monomer is preferably controlled to obtain the composition of each structural unit as described above. The polymerization solvent can be appropriately selected from solvents capable of dissolving each monomer. For example, water, dimethyl sulfoxide, chlorobenzene, tetrahydrofuran, etc., can be used; from the viewpoint of monomer solubility, dimethyl sulfoxide and chlorobenzene are preferred. One of the above polymerization solvents can be used alone, or it can be used as a mixture of two or more solvents. In the above polymerization, the polymerization conditions are not particularly limited, as long as the copolymerization is carried out. For example, the polymerization temperature is preferably set to 30–150°C, more preferably 40–100°C. Furthermore, the polymerization time is preferably 30 minutes to 24 hours, more preferably 3 to 15 hours. The polymerization is carried out in an inert atmosphere such as a nitrogen atmosphere or an argon atmosphere.
[0076] In addition, chain transfer agents, polymerization rate regulators, surfactants, water-soluble polymers, water-soluble inorganic compounds (alkali metal salts, alkali metal hydroxides, polyvalent metal salts, and non-reducing alkali metal salt pH buffers, etc.), inorganic acids, inorganic acid salts, organic acids and organic acid salts, and other additives may be used as needed during copolymerization. After polymerization, purification is preferably carried out using conventional purification methods such as reprecipitation, dialysis, ultrafiltration, and extraction.
[0077] The structural unit (A-2) is a structural unit derived from a hydrophilic monomer having at least one of a carboxyl group and a salt having a carboxyl group. A copolymer having a structural unit (A-2) derived from a hydrophilic monomer having a carboxyl group can also be obtained by alkali treatment, replacing all or part of the structural unit derived from the hydrophilic monomer having a carboxyl group with a structural unit derived from a salt having a carboxyl group. The alkali treatment described above can be performed, for example, by mixing a solution containing a copolymer comprising a structural unit (A-2) containing a structural unit derived from a carboxyl group (e.g., a copolymer comprising a structural unit (A-2) derived from acrylic acid) with an aqueous solution containing an alkaline substance (e.g., sodium bicarbonate or calcium hydroxide). In the case of forming a lubricating layer comprising a copolymer comprising a structural unit (A-2) containing a hydrophilic monomer having a carboxyl group, the copolymer obtained as described above can be used to prepare a coating liquid for forming the lubricating layer.
[0078] It should be noted that, in the case of forming a lubricating layer comprising a copolymer having a structural unit (A-2) derived from a hydrophilic monomer having a carboxyl group, the lubricating precursor layer may also be formed by treating the lubricating precursor layer with an aqueous solution containing an alkaline substance (e.g., immersing the lubricating precursor layer in an aqueous solution of sodium bicarbonate) after forming a coating liquid comprising a copolymer having a structural unit (A-2) derived from a hydrophilic monomer having a carboxyl group, as described in WO 2015 / 029625.
[0079] In the above-described alkaline treatment, only the carboxyl group in structural unit (A-2) is converted into a salt of the carboxyl group. Therefore, through this treatment, the content (mol%) of structural unit (A-2) relative to the total amount of structural units (A-1) and (A-2), and the content (mol) of structural unit (A) relative to 1 mol of structural unit (B) do not change.
[0080] (Other ingredients) The lubricating layer must contain the aforementioned copolymer. In addition to the copolymer, the lubricating layer may also contain other components. There are no particular restrictions on these other components. For example, in the case of medical devices such as catheters intended for insertion into body cavities or tubes, examples include anticancer agents, immunosuppressants, antibiotics, antirheumatic drugs, antithrombotic drugs, HMG-CoA reductase inhibitors, ACE inhibitors, calcium channel blockers, antilipidemic drugs, integrin inhibitors, antiallergic agents, antioxidants, GPIIbIIIa antagonists, retinoids, flavonoids, carotenoids, lipid modifiers, DNA synthesis inhibitors, tyrosine kinase inhibitors, antiplatelet drugs, vascular smooth muscle proliferation inhibitors, anti-inflammatory drugs, biologically derived materials, interferon, and NO production promoters (physiologically active substances). There are no particular restrictions on the amount of these other components added; the commonly used amounts also apply. Ultimately, the amount of these other components added is appropriately selected by the attending physician based on the severity of the disease being treated and the patient's weight. Preferably, the lubricating layer does not contain any other components (i.e., the lubricating layer is substantially composed of the aforementioned copolymer). Specifically, the content of other components is preferably less than 10% by mass (converted to solid components) relative to the mass of the lubricating layer, more preferably less than 5% by mass (converted to solid components), and particularly preferably the lubricating layer does not contain any other components (i.e., the lubricating layer is composed of the aforementioned copolymer).
[0081] <Methods for Manufacturing Medical Devices> The method for manufacturing the medical device of the present invention uses the above-mentioned copolymer and other components as needed to form a lubricating layer. There are no particular limitations, and it can be applied in the same way as known methods or with appropriate modifications to known methods. The preferred method for manufacturing the medical device of the present invention is as follows: adding and mixing the copolymer of the present invention and other components as needed in a solvent to prepare a solution containing the copolymer (hereinafter also referred to as "coating liquid") ((I) Coating liquid preparation step); coating the coating liquid onto a substrate layer to form a coating film on the substrate layer ((II) Coating film formation step); heat-treating the coating film to form a lubricating layer on the substrate layer ((III) Lubricating layer formation step).
[0082] The preferred implementation methods for each process are described below.
[0083] (I) Coating solution preparation process In this process, a solution (coating solution) comprising the copolymer, a solvent, and other components as needed is prepared. Here, there are no particular limitations on the solvent used in the preparation of the coating solution; it can be appropriately selected based on the type of copolymer (and, if other components are used). Specifically, examples of solvents include, but are not limited to, alcohols such as water, methanol, ethanol, isopropanol, and ethylene glycol; ketones such as acetone, methyl ethyl ketone, and cyclohexanone; esters such as ethyl acetate; halides such as chloroform; alkanes such as hexane; ethers such as tetrahydrofuran and butyl ether; aromatics such as benzene and toluene; amides such as N,N-dimethylformamide; and sulfoxides such as dimethyl sulfoxide. One of the above solvents can be used alone, or two or more can be used in combination.
[0084] After the copolymer and other components as needed are added to the solvent, stirring may be performed as needed to promote dissolution or dispersion.
[0085] The concentration of the copolymer in the coating solution is not particularly limited. For example, the concentration of the copolymer in the coating solution is 0.5% by mass or more and 50% by mass or less, preferably 1% by mass or more and 10% by mass or less. If the copolymer concentration is within the above range, the resulting lubricating layer can fully exert the effects of the present invention. Furthermore, a lubricating layer of the desired thickness can be easily obtained with a single coating, and the viscosity of the solution is within an appropriate range, which is preferred from the perspective of operability (e.g., the coatability of the coating solution) and production efficiency. However, even if it exceeds the above range, it can be fully utilized as long as it does not affect the effectiveness of the present invention.
[0086] (II) Coating Formation Process In this process, the coating liquid prepared in (I) above is applied to the substrate layer to form a coating film on the substrate layer. Here, the substrate layer is the same as described above, so the description is omitted here.
[0087] There are no particular limitations on the method of applying (coating) the copolymer solution (coating liquid) to the surface of the substrate layer. Conventionally known methods such as coating / printing, dipping, spraying, spin coating, sponge coating with mixed solution impregnation, bar coating (e.g., wire rod coating), die coating, reverse coating, comma coating, gravure coating, and doctor blade coating can be used. Among these, dipping, spraying, and bar coating are preferred.
[0088] It should be noted that when forming a coating (and thus a lubricating layer; the same applies below) on the narrow inner surface of a conduit or similar material, the substrate layer can be immersed in the coating solution, and degassing can be performed by depressurizing the system. Degassing by depressurizing allows the solution to quickly penetrate the narrow inner surface, promoting coating formation. Furthermore, when forming a coating only on a portion of the substrate layer, by immersing only that portion of the substrate layer in the coating solution and applying the coating solution to that portion of the substrate layer, a coating can be formed on the desired surface area of the substrate layer.
[0089] In cases where it is difficult to immerse only a portion of the substrate layer in the coating liquid, the surface portion of the substrate layer for which a coating is not required is pre-protected (coated, etc.) with suitable removable (installable / removable) parts or materials. The substrate layer is then immersed in the coating liquid, the coating liquid is applied to the substrate layer, and the protective parts (materials) for the surface portion of the substrate layer for which a lubricating layer is not required are removed. This allows a coating to be formed on the desired surface portion of the substrate layer. However, this invention is not limited to these methods, and conventionally known methods can be appropriately utilized to form the coating. For example, in cases where it is difficult to immerse only a portion of the substrate layer in the coating liquid, other coating methods can be applied instead of immersion (e.g., methods for applying a coating liquid to a specified surface portion of a medical device using a sprayer, bar coater, die coater, reverse coater, comma coater, gravure coater, spray coater, doctor blade, etc.). It should be noted that, in terms of the structure of medical devices, where both the outer and inner surfaces of cylindrical devices need to have a lubricating layer, the immersion method is preferred from the perspective of being able to coat both the outer and inner surfaces in one go.
[0090] The amount of coating liquid applied is preferably selected in such a way that the thickness (dry film thickness) of the resulting lubricating layer is within the range described above.
[0091] It should be noted that before applying the coating solution, the substrate surface can be pre-treated by methods such as ultraviolet irradiation, plasma treatment, corona discharge treatment, flame treatment, oxidation treatment, silane coupling treatment, phosphoric acid coupling treatment, and surfactant treatment. When the coating solution's solvent is only water, it is difficult to apply the coating solution to a hydrophobic substrate surface. However, by subjecting the substrate surface to plasma treatment or surfactant treatment, the substrate surface can be made hydrophilic. This improves the wettability of the coating solution on the substrate surface, enabling the formation of a uniform lubricating layer.
[0092] (III) Lubricating layer formation process In this process, the coating film formed in (II) above is heat-treated to form a lubricating layer on the substrate layer. During the heat treatment, the epoxy groups present in structural unit (B) interact with other structural units (B) within the copolymer or with structural units (B) in adjacent copolymers, forming crosslinking points between molecules. In addition to the above interactions, a portion of the epoxy groups present in structural unit (B) undergoes ring-opening via heat treatment using carboxyl groups (salts) within the copolymer or with carboxyl groups (salts) in adjacent copolymers as catalysts, forming chemical crosslinks with other epoxy groups or carboxyl groups (salts). It should be noted that if the surface of the substrate layer has functional groups capable of reacting with epoxy groups, the epoxy groups present in structural unit (B) can also form crosslinks with these functional groups in the substrate layer.
[0093] The heat treatment conditions can be appropriately selected based on the types of monomers constituting the copolymer (especially hydrophilic monomers (A-2) and hydrophobic monomers). The heat treatment temperature is preferably 60°C to 170°C, more preferably 80°C to 150°C. Furthermore, the heat treatment time is preferably 10 minutes to 24 hours, more preferably 30 minutes to 5 hours. Under such conditions, the aggregation of structural units (B) can be promoted during heat treatment, and the chemical cross-linking of epoxy groups and the chemical cross-linking of carboxyl groups and epoxy groups can be promoted by allowing the carboxyl groups of structural unit (A-2) to act as catalysts. In addition, the pressure conditions during heat treatment are not limited; it can be carried out under normal pressure (atmospheric pressure), pressurized conditions, or reduced pressure. For example, an oven (heat treatment furnace) or a reduced pressure heat treatment machine can be used for heat treatment. The heat treatment process can be performed only once, or the heat treatment conditions can be separated and repeated multiple times.
[0094] The lubricating layer is formed on the substrate layer in the manner described above. It should be noted that the lubricating layer on the substrate layer can also be cleaned after the heat treatment process described above.
[0095] The lubricating layer obtained by the above method can exhibit excellent lubricity and durability (lubricity maintenance and sliding durability) even under harsh conditions. Therefore, medical devices with such a lubricating layer can also be applied to complex lesion sites.
[0096] [Uses of medical devices] The medical device of the present invention exhibits excellent lubricity and durability of its lubricating layer. The medical device of the present invention is used in contact with bodily fluids, blood, etc. In aqueous liquids such as bodily fluids and physiological saline, the surface of the lubricating layer is lubricating, improving operability, reducing damage to tissue mucosa, and maintaining lubricity over a long period. Therefore, the medical device is suitable for use as catheters, stents, guidewires, etc., in vascular applications. Specifically, in one embodiment of the present invention, the medical device is a catheter, stent, or guidewire. Other medical devices include...
[0097] (a) Gastric tubes, feeding tubes, and tube feeding tubes, etc., which are inserted or left in the digestive organs through the mouth or nose; (b) Catheters that are inserted or left in the respiratory tract or trachea through the mouth or nose, such as oxygen catheters, oxygen delivery tubes, endotracheal tubes or cuffs, tracheostomy tubes or cuffs, endotracheal suction catheters, etc. (c) Catheters such as urethral catheters, urinary catheters, and urethral balloon catheters that are inserted into or left in place in the urethra or ureter; (d) Catheters such as suction catheters, drainage catheters, and rectal catheters that are inserted into or left in place in various body cavities, organs, and tissues; (e) Catheters inserted into or left in blood vessels, such as indwelling needles, IVH catheters, thermodilution catheters, angiography catheters, vasodilators and dilators or guides, or guidewires and catheterization needles used with these catheters; (f) Artificial trachea, artificial bronchi, etc.; (g) Medical devices used for extracorporeal circulation therapy (artificial lungs, artificial hearts, artificial kidneys, etc.) and their circuits.
[0098] Example The effects of the present invention will be illustrated using the following examples and comparative examples. However, the technical scope of the present invention should not be construed as limited to the following examples, and examples obtained by appropriately combining the technical means disclosed in the various examples are also included within the scope of the present invention. It should be noted that, in the following examples, unless otherwise specified, the operation is carried out at room temperature (25°C). In addition, unless otherwise specified, "%" and "parts" refer to "mass %" and "parts by mass," respectively.
[0099] Synthesis Example 1: Synthesis of Copolymer 1 After adding 29.7 g of triethylene glycol dropwise to 72.3 g of adipic dichloride at 50 °C, the hydrochloric acid was removed under reduced pressure at 50 °C for 3 hours. Then, 4.5 g of methyl ethyl ketone was added to 22.5 g of the resulting low-polyester. This solution was then added dropwise to a solution composed of 5 g of sodium hydroxide, 6.93 g of 31% hydrogen peroxide aqueous solution, 0.44 g of dioctyl phosphate surfactant, and 120 g of water. The reaction was carried out at -5 °C for 20 minutes. The resulting product was repeatedly washed with water and methanol, and then dried to obtain polyperoxide (PPO) with multiple peroxide groups within the molecule. Next, using benzene as a solvent, 0.5 g of PPO as a polymerization initiator and 9.5 g of glycidyl methacrylate (GMA) as a hydrophobic monomer were stirred at 65 °C under reduced pressure for 2 hours and polymerized. The reactants were then reprecipitated using diethyl ether to obtain polyGMA (PPO-GMA) with peroxide groups within the molecule.
[0100] Next, 0.83 g of the obtained PPO-GMA (equivalent to 5.81 mmol of GMA) was used as a polymerization initiator. 6.33 g (63.88 mmol) of N,N-dimethylacrylamide (DMAA) and 0.42 g (5.81 mmol) of acrylic acid (AA) were dissolved in a mixed solvent of chlorobenzene and dimethyl sulfoxide (DMSO) (chlorobenzene:DMSO = 1:1 (mass ratio)). Polymerization was carried out under a nitrogen atmosphere, heated to 75°C and maintained for 3 hours. The reactants were then reprecipitated using tert-butyl methyl ether and recovered to obtain copolymer 1 composed of DMAA, AA, and GMA. 13 C-NMR was used to determine the ratio of DMAA:AA:GMA in the obtained copolymer 1, and the result was that the ratio (molar ratio) of DMAA:AA:GMA was 11:1:1.
[0101] Synthesis Example 2: Synthesis of Copolymer 2 The same procedure as in Synthesis Example 1 was followed to obtain polyGMA (PPO-GMA).
[0102] Next, 0.71 g of the obtained PPO-GMA (equivalent to 4.98 mmol of GMA) was used as a polymerization initiator. 4.93 g (49.76 mmol) of N,N-dimethylacrylamide (DMAA) and 1.79 g (24.88 mmol) of acrylic acid (AA) were dissolved in a mixed solvent of chlorobenzene and dimethyl sulfoxide (DMSO) (chlorobenzene:DMSO = 1:1 (mass ratio)). The mixture was heated to 75°C and held for 3 hours under a nitrogen atmosphere to carry out polymerization, yielding copolymer 2. Following the same method as in Synthesis Example 1, the DMAA:AA:GMA ratio of the obtained copolymer 2 was determined, and the result was a DMAA:AA:GMA molar ratio of 9:4:1.
[0103] Synthesis Example 3: Synthesis of Copolymer 3 The same procedure as in Synthesis Example 1 was followed to obtain polyGMA (PPO-GMA).
[0104] Next, 0.45 g of the obtained PPO-GMA (equivalent to 3.14 mmol of GMA) was used as a polymerization initiator. 6.22 g (62.73 mmol) of N,N-dimethylacrylamide (DMAA), a hydrophilic monomer, and 0.45 g (6.27 mmol) of acrylic acid (AA) were dissolved in a mixed solvent of chlorobenzene and dimethyl sulfoxide (DMSO) (chlorobenzene:DMSO = 1:1 (mass ratio)). The mixture was heated to 75°C and held for 5 hours under a nitrogen atmosphere to carry out polymerization, thereby obtaining copolymer 3. Following the same method as in Synthesis Example 1, the DMAA:AA:GMA ratio of the obtained copolymer 3 was determined, and the result was a DMAA:AA:GMA molar ratio of 20:2:1.
[0105] Synthesis Example 4: Synthesis of Copolymer 4 The same procedure as in Synthesis Example 1 was followed to obtain polyGMA (PPO-GMA).
[0106] Next, 0.28 g of the obtained PPO-GMA (equivalent to 1.99 mmol of GMA) was used as a polymerization initiator. 5.92 g (59.71 mmol) of N,N-dimethylacrylamide (DMAA) and 0.72 g (9.95 mmol) of acrylic acid (AA), acting as hydrophilic monomers, were dissolved in a mixed solvent of chlorobenzene and dimethyl sulfoxide (DMSO) (chlorobenzene:DMSO = 1:1 (mass ratio)). The mixture was heated to 75°C and held for 5 hours under a nitrogen atmosphere to carry out polymerization, yielding copolymer 4. Following the same method as in Synthesis Example 1, the DMAA:AA:GMA ratio of the obtained copolymer 4 was determined, and the result was a DMAA:AA:GMA molar ratio of 29:5:1.
[0107] Synthesis Example 5: Synthesis of Copolymer 5 The same procedure as in Synthesis Example 1 was followed to obtain polyGMA (PPO-GMA).
[0108] Next, 0.20 g of the obtained PPO-GMA (equivalent to 1.44 mmol of GMA) was used as a polymerization initiator. 6.41 g (64.68 mmol) of N,N-dimethylacrylamide (DMAA) and 0.21 g (2.87 mmol) of acrylic acid (AA) were dissolved in a mixed solvent of chlorobenzene and dimethyl sulfoxide (DMSO) (chlorobenzene:DMSO = 1:1 (mass ratio)). The mixture was heated to 75°C and held for 5 hours under a nitrogen atmosphere to carry out polymerization, yielding copolymer 5. Following the same method as in Synthesis Example 1, the DMAA:AA:GMA ratio of the obtained copolymer 5 was determined, and the result was a DMAA:AA:GMA molar ratio of 44:2:1.
[0109] Synthesis Example 6: Synthesis of Copolymer 6 The same procedure as in Synthesis Example 1 was followed to obtain polyGMA (PPO-GMA).
[0110] Next, 0.20 g of the obtained PPO-GMA (equivalent to 1.37 mmol of GMA) was used as a polymerization initiator. 6.12 g (61.76 mmol) of N,N-dimethylacrylamide (DMAA) and 0.50 g (6.86 mmol) of acrylic acid (AA) were dissolved in a mixed solvent of chlorobenzene and dimethyl sulfoxide (DMSO) (chlorobenzene:DMSO = 1:1 (mass ratio)). The mixture was heated to 75°C and held for 5 hours under a nitrogen atmosphere to carry out polymerization, yielding copolymer 6. Following the same method as in Synthesis Example 1, the DMAA:AA:GMA ratio of the obtained copolymer 6 was determined, and the result was a DMAA:AA:GMA molar ratio of 43:4:1.
[0111] Synthesis Example 7: Synthesis of Copolymer 7 The same procedure as in Synthesis Example 1 was followed to obtain polyGMA (PPO-GMA).
[0112] Next, 0.18 g of the obtained PPO-GMA (equivalent to 1.28 mmol of GMA) was used as a polymerization initiator. 5.70 g (57.45 mmol) of N,N-dimethylacrylamide (DMAA) and 0.92 g (12.77 mmol) of acrylic acid (AA) were dissolved in a mixed solvent of chlorobenzene and dimethyl sulfoxide (DMSO) (chlorobenzene:DMSO = 1:1 (mass ratio)). The mixture was heated to 75°C and held for 5 hours under a nitrogen atmosphere to carry out polymerization, yielding copolymer 7. Following the same method as in Synthesis Example 1, the DMAA:AA:GMA ratio of the obtained copolymer 7 was determined, and the result was a DMAA:AA:GMA molar ratio of 41:8:1.
[0113] Synthesis Example 8: Synthesis of Copolymer 8 The same procedure as in Synthesis Example 1 was followed to obtain polyGMA (PPO-GMA).
[0114] Next, 0.15 g of the obtained PPO-GMA (equivalent to 1.05 mmol of GMA) was used as a polymerization initiator. 6.23 g (62.85 mmol) of N,N-dimethylacrylamide (DMAA), a hydrophilic monomer, and 0.38 g (5.24 mmol) of acrylic acid (AA) were dissolved in a mixed solvent of chlorobenzene and dimethyl sulfoxide (DMSO) (chlorobenzene:DMSO = 1:1 (mass ratio)). The mixture was heated to 75°C and held for 5 hours under a nitrogen atmosphere to carry out polymerization, yielding copolymer 8. Following the same method as in Synthesis Example 1, the DMAA:AA:GMA ratio of the obtained copolymer 8 was determined, and the result was a DMAA:AA:GMA molar ratio of 54:4:1.
[0115] Synthesis Example 9: Synthesis of Copolymer 9 The same procedure as in Synthesis Example 1 was followed to obtain polyGMA (PPO-GMA).
[0116] Next, 0.12 g of the obtained PPO-GMA (equivalent to 0.85 mmol of GMA) was used as a polymerization initiator. 6.30 g (63.52 mmol) of N,N-dimethylacrylamide (DMAA) and 0.31 g (4.23 mmol) of acrylic acid (AA) were dissolved in a mixed solvent of chlorobenzene and dimethyl sulfoxide (DMSO) (chlorobenzene:DMSO = 1:1 (mass ratio)). The mixture was heated to 75°C and held for 8 hours under a nitrogen atmosphere to carry out polymerization, yielding copolymer 9. Following the same method as in Synthesis Example 1, the DMAA:AA:GMA ratio of the obtained copolymer 9 was determined, and the result was a DMAA:AA:GMA ratio (molar ratio) of 70:4:1 (molar ratio).
[0117] Synthesis Example 10: Synthesis of Copolymer 10 The same procedure as in Synthesis Example 1 was followed to obtain polyGMA (PPO-GMA).
[0118] Next, 0.10 g of the obtained PPO-GMA (equivalent to 0.71 mmol of GMA) was used as a polymerization initiator. 6.34 g (63.97 mmol) of N,N-dimethylacrylamide (DMAA), a hydrophilic monomer, and 0.26 g (3.55 mmol) of acrylic acid (AA) were dissolved in a mixed solvent of chlorobenzene and dimethyl sulfoxide (DMSO) (chlorobenzene:DMSO = 1:1 (mass ratio)). The mixture was heated to 75°C and held for 8 hours under a nitrogen atmosphere to carry out polymerization, yielding copolymer 10. Following the same method as in Synthesis Example 1, the DMAA:AA:GMA ratio of the obtained copolymer 10 was determined, and the result was a DMAA:AA:GMA ratio (molar ratio) of 82:4:1 (molar ratio).
[0119] Synthesis Example 11: Synthesis of Copolymer 11 The same procedure as in Synthesis Example 1 was followed to obtain polyGMA (PPO-GMA).
[0120] Next, 1.68 g of the obtained PPO-GMA (equivalent to 11.84 mmol of GMA) was used as a polymerization initiator. 5.87 g (59.19 mmol) of N,N-dimethylacrylamide (DMAA) and 0.85 g (11.84 mmol) of acrylic acid (AA) were dissolved in a mixed solvent of chlorobenzene and dimethyl sulfoxide (DMSO) (chlorobenzene:DMSO = 1:1 (mass ratio)). The mixture was heated to 75°C and held for 5 hours under a nitrogen atmosphere to carry out polymerization, yielding copolymer 11. Following the same method as in Synthesis Example 1, the DMAA:AA:GMA ratio of the obtained copolymer 11 was determined, and the result was a DMAA:AA:GMA ratio (molar ratio) of 5:1:1 (molar ratio).
[0121] Synthesis Example 12: Synthesis of Copolymer 12 The same procedure as in Synthesis Example 1 was followed to obtain polyGMA (PPO-GMA).
[0122] Next, 0.54 g of the obtained PPO-GMA (equivalent to 3.79 mmol of GMA) was used as a polymerization initiator, and 4.51 g (45.45 mmol) of N,N-dimethylacrylamide (DMAA), as a hydrophilic monomer, was dissolved in chlorobenzene solvent. The mixture was heated to 80°C and maintained for 7 hours under a nitrogen atmosphere to carry out polymerization, yielding copolymer 12. 1H-NMR was used to determine the DMAA:GMA ratio of the obtained copolymer 12, and the result was that the DMAA:GMA ratio (molar ratio) was 12:1.
[0123] Synthesis Example 13: Synthesis of Copolymer 13 The same procedure as in Synthesis Example 1 was followed to obtain polyGMA (PPO-GMA).
[0124] Next, 0.10 g of the obtained PPO-GMA (equivalent to 0.72 mmol of GMA) was used as a polymerization initiator. 6.44 g (64.98 mmol) of N,N-dimethylacrylamide (DMAA), a hydrophilic monomer, and 0.16 g (2.17 mmol) of acrylic acid (AA) were dissolved in a mixed solvent of chlorobenzene and dimethyl sulfoxide (DMSO) (chlorobenzene:DMSO = 1:1 (mass ratio)). The mixture was heated to 75°C and held for 8 hours under a nitrogen atmosphere to carry out polymerization, yielding copolymer 13. Following the same method as in Synthesis Example 1, the DMAA:AA:GMA ratio of the obtained copolymer 13 was determined, and the result was a DMAA:AA:GMA molar ratio of 80:2:1.
[0125] Synthesis Example 14: Synthesis of Copolymer 14 The same procedure as in Synthesis Example 1 was followed to obtain polyGMA (PPO-GMA).
[0126] Next, 0.09 g of the obtained PPO-GMA (equivalent to 0.64 mmol of GMA) was used as a polymerization initiator. 6.36 g (64.20 mmol) of N,N-dimethylacrylamide (DMAA), a hydrophilic monomer, and 0.23 g (3.21 mmol) of acrylic acid (AA) were dissolved in a mixed solvent of chlorobenzene and dimethyl sulfoxide (DMSO) (chlorobenzene:DMSO = 1:1 (mass ratio)). The mixture was heated to 75°C and held for 8 hours under a nitrogen atmosphere to carry out polymerization, yielding copolymer 14. Following the same method as in Synthesis Example 1, the DMAA:AA:GMA ratio of the obtained copolymer 14 was determined, and the result was a DMAA:AA:GMA molar ratio of 87:4:1.
[0127] Synthesis Example 15: Synthesis of Copolymer 15 The same procedure as in Synthesis Example 1 was followed to obtain polyGMA (PPO-GMA).
[0128] Next, 0.91 g of the obtained PPO-GMA (equivalent to 6.38 mmol of GMA) was used as a polymerization initiator. 3.80 g (38.30 mmol) of N,N-dimethylacrylamide (DMAA) and 2.76 g (38.30 mmol) of acrylic acid (AA) were dissolved in a mixed solvent of chlorobenzene and dimethyl sulfoxide (DMSO) (chlorobenzene:DMSO = 1:1 (mass ratio)). The mixture was heated to 75°C and maintained for 3 hours under a nitrogen atmosphere. After the reaction was completed, yellowing was observed in the polymerization solution, and copolymer 15 (DMAA:AA:GMA ratio (molar ratio) = 6:6:1 (charge ratio)) was not obtained.
[0129] Reference Example 1 The gel fractions of copolymers 6 and 12 obtained in the above synthetic examples 6 and 12 were determined according to the following method. It should be noted that gel fraction refers to an indicator of the degree of crosslinking (crosslinking density) of the copolymer under specific conditions. Specifically, gel fraction refers to the ratio of the weight of the gel (the weight of the insoluble component after dissolving the copolymer in a specific solvent) to the weight of the copolymer before dissolution. That is, the gel fraction shown here indicates the ease with which the copolymer cures under the same temperature conditions (130°C, 2 hours) (the crosslinking density of the copolymer in the lubricating layer). For example, a high gel fraction suggests that heat treatment facilitates the curing of the copolymer, resulting in high durability of the lubricating layer.
[0130] [Determination of gel fraction] (Preparation of the curing film) After adding copolymer 6 or copolymer 12 to dimethylformamide (DMF), the mixture was stirred for 1 hour to obtain a coating solution with a concentration of 8% by mass. Then, approximately 5 ml of this coating solution was evenly spread on a 75 mm diameter PFA culture dish and heated at 130°C for 2 hours to form a cured film on the culture dish.
[0131] (Determination of gel fraction) The cured film obtained above is cut into 3-5 mm square pieces and used as samples.
[0132] Add 50 mg of the sample to a 50 ml sample tube, followed by 10 g of dimethylformamide (DMF). Then, heat the sample tube on a hot plate at 100 °C for 1 hour. Pass the heated contents through a folded metal mesh (#150, 100 mm in diameter) to separate the solid components from the DMF. Immerse the mesh with the solid components attached in approximately 50 ml of acetone for 10 minutes, replacing the solvent from DMF with acetone, and then dry under reduced pressure at 130 °C for 3 hours. After drying, weigh the sample along with the metal mesh, and the difference between the dry mass and the pre-measured mass of the metal mesh is taken as the dried mass of the sample (mg). Divide the dried mass of the sample (mg) by the initial mass (50 mg) to obtain the percentage (%) [= (dried mass of sample (mg) × 100) / initial mass (50 mg)] as the gel fraction (%).
[0133] The results are shown in Figure 1 It should be noted that the above measurements were performed three times for each sample (N=3), and the average value was taken as the mean. Figure 1 The gel fraction is shown. Additionally, in Figure 1 In addition to the gel fraction ( Figure 1 In addition to the white column in the image, the sliding resistance values (gf) of samples 6 and 12 measured in the following text are also recorded for the 20th time. Figure 1 (The black column in the middle).
[0134] Depend on Figure 1 It can be seen that, compared with copolymer 12 (DMAA:GMA=12:1 (molar ratio)) (gel fraction=57.7%), copolymer 6 (DMAA:AA:GMA=43:4:1 (molar ratio)) (gel fraction=79.0%) shows a significantly higher gel fraction.
[0135] The proportion of structural unit (B) relative to all structural units constituting copolymer 6 (the proportion of GMA-derived structural units relative to all structural units constituting copolymer 6 = approximately 2.1 mol%) is lower than the proportion of structural unit (B) relative to all structural units constituting copolymer 12 (the proportion of GMA-derived structural units relative to all structural units constituting copolymer 12 = approximately 7.7 mol%). Therefore, generally speaking, in copolymer 6, compared to copolymer 12, the proportion of other structural units (B) surrounding the epoxy groups present in structural unit (B) is smaller, thus the intermolecular crosslinking point formation rate decreases, and the gel fraction should decrease.
[0136] However, as Figure 1The results show that copolymer 6 exhibits a significantly higher gel fraction compared to copolymer 12. These results suggest that the carboxyl groups (salts) present in the structural unit (A-2) of the copolymer (carboxyl groups present in acrylic acid) act as catalysts through heat treatment, causing ring-opening of the epoxy groups present in structural unit (B), promoting chemical cross-linking between epoxy groups and between epoxy groups and carboxyl groups (salts).
[0137] Therefore, it is expected that the copolymer involved in this invention, by introducing structural units (A-2) having carboxyl groups (salts), can promote the chemical crosslinking of epoxy groups with each other, as well as the chemical crosslinking of epoxy groups with carboxyl groups (salts), thereby improving the film strength (crosslinking density) of the lubricating layer. Therefore, it is expected that the sliding durability (lubrication maintenance) of the lubricating layer can be further improved.
[0138] In addition to the results described above, the sliding resistance value (5.5 gf) of sample 6, which has a lubricating layer comprising copolymer 6 having structural unit (A-2), in the 20th test was significantly lower than that of sample 12, which has a lubricating layer comprising copolymer 12 that does not have the aforementioned structural unit (A-2), in the 20th test (19.2 gf). That is, sample 6 exhibits superior lubricity compared to sample 12. Here, the sliding resistance value (19.2 gf) of sample 12, which has a lubricating layer comprising copolymer 12, in the 20th test was also significantly higher than that of sample 1, which has a lubricating layer comprising copolymer 1, in the 20th test (13.1 gf). Therefore, it is speculated that one reason for this improved lubricity is that the presence of structural unit (A-2) in the copolymer, particularly structural unit (A-2) having a carboxyl group (salt) that does not form a chemical bond with the epoxy group, further imparts hydrophilicity and water absorption to the lubricating layer. Therefore, it is expected that the copolymer of the present invention can further improve lubricity by introducing structural unit (A-2) having a carboxyl group (salt).
[0139] Example 1 After adding 0.5g of copolymer 1 to 12.3g of acetone, 6.19g of 0.52% sodium bicarbonate aqueous solution was added and stirred for 1 hour to obtain coating solution 1.
[0140] Next, 0.4mm of nylon 12 (DAIAMID L1940W, manufactured by Polyplastics-Evonik Co., Ltd.) was used. The above-mentioned coating liquid 1 was dipped onto the tube substrate at a speed of 50 mm / sec and then heated at 120°C for 2 hours to obtain sample 1 with a lubricating layer (dry film thickness: about 1 μm) formed on the tube substrate.
[0141] Example 2 After adding 0.5g of copolymer 2 to 12.3g of acetone, 6.29g of 2.02% sodium bicarbonate aqueous solution was added and stirred for 1 hour to obtain coating solution 2.
[0142] Instead of coating liquid 1 in Example 1, the above-mentioned coating liquid 2 was used. Otherwise, the same procedure as in Example 1 was followed to obtain sample 2 with a lubricating layer formed on the tube substrate.
[0143] Example 3 After adding 0.5g of copolymer 3 to 12.3g of acetone, 6.19g of 0.60% sodium bicarbonate aqueous solution was added, and the mixture was stirred for 1 hour to obtain coating solution 3.
[0144] Instead of coating liquid 1 in Example 1, the above-mentioned coating liquid 3 was used. Otherwise, the same procedure as in Example 1 was followed to obtain sample 3 in which a lubricating layer was formed on the tube substrate.
[0145] Example 4 After adding 0.5g of copolymer 4 to 12.3g of acetone, 6.22g of 1.00% sodium bicarbonate aqueous solution was added and stirred for 1 hour to obtain coating solution 4.
[0146] Instead of coating liquid 1 in Example 1, the above-mentioned coating liquid 4 was used. Otherwise, the same procedure as in Example 1 was followed to obtain sample 4 in which a lubricating layer was formed on the tube substrate.
[0147] Example 5 After adding 0.5g of copolymer 5 to 12.3g of acetone, 6.19g of 0.29% sodium bicarbonate aqueous solution was added, and the mixture was stirred for 1 hour to obtain coating solution 5.
[0148] Instead of coating liquid 1 in Example 1, the above-mentioned coating liquid 5 was used. Otherwise, the same procedure as in Example 1 was followed to obtain sample 5 in which a lubricating layer was formed on the tube substrate.
[0149] Example 6 After adding 0.5g of copolymer 6 to 12.3g of acetone, 6.20g of 0.58% sodium bicarbonate aqueous solution was added, and the mixture was stirred for 1 hour to obtain coating solution 6.
[0150] Instead of coating liquid 1 in Example 1, the above-mentioned coating liquid 6 was used. Otherwise, the same procedure as in Example 1 was followed to obtain sample 6 in which a lubricating layer was formed on the tube substrate.
[0151] Example 7 After adding 0.5g of copolymer 7 to 12.3g of acetone, 6.24g of 1.13% sodium bicarbonate aqueous solution was added, and the mixture was stirred for 1 hour to obtain coating solution 7.
[0152] Instead of coating liquid 1 in Example 1, the above-mentioned coating liquid 7 was used. Otherwise, the same procedure as in Example 1 was followed to obtain sample 7 with a lubricating layer formed on the tube substrate.
[0153] Example 8 After adding 0.5g of copolymer 8 to 12.3g of acetone, 6.18g of 0.47% sodium bicarbonate aqueous solution was added, and the mixture was stirred for 1 hour to obtain coating solution 8.
[0154] Instead of coating liquid 1 in Example 1, the above-mentioned coating liquid 8 was used. Otherwise, the same procedure as in Example 1 was followed to obtain sample 8 with a lubricating layer formed on the tube substrate.
[0155] Example 9 After adding 0.5g of copolymer 9 to 12.3g of acetone, 6.19g of 0.37% sodium bicarbonate aqueous solution was added, and the mixture was stirred for 1 hour to obtain coating solution 9.
[0156] Instead of coating liquid 1 in Example 1, the above-mentioned coating liquid 9 was used. Otherwise, the same procedure as in Example 1 was followed to obtain sample 9 with a lubricating layer formed on the tube substrate.
[0157] Example 10 After adding 0.5g of copolymer 10 to 12.3g of acetone, 6.19g of 0.32% sodium bicarbonate aqueous solution was added and stirred for 1 hour to obtain coating liquid 10.
[0158] Instead of coating liquid 1 in Example 1, the above-mentioned coating liquid 10 was used. Otherwise, the same procedure as in Example 1 was followed to obtain sample 10 with a lubricating layer formed on the tube substrate.
[0159] Comparative Example 1 After adding 0.5g of copolymer 11 to 12.3g of acetone, 6.23g of 0.95% sodium bicarbonate aqueous solution was added and stirred for 1 hour to obtain coating solution 11.
[0160] Instead of the coating liquid 1 in Example 1, the above-mentioned coating liquid 11 was used. Otherwise, the same procedure as in Example 1 was followed to obtain a sample 11 in which a lubricating layer was formed on the tube substrate.
[0161] Comparative Example 2 0.6 g of copolymer 12 was dissolved in 19.4 g of dimethylformamide (DMF) to obtain coating solution 12.
[0162] Instead of coating liquid 1 in Example 1, the above-mentioned coating liquid 12 was used, and the heating temperature was changed to 130°C. Otherwise, the operation was the same as in Example 1, and a sample 12 with a lubricating layer formed on the tube substrate was obtained.
[0163] Comparative Example 3 After adding 0.5g of copolymer 13 to 12.3g of acetone, 6.16g of 0.17% sodium bicarbonate aqueous solution was added and stirred for 1 hour to obtain coating solution 13.
[0164] Instead of coating liquid 1 in Example 1, the above-mentioned coating liquid 13 was used. Otherwise, the same procedure as in Example 1 was followed to obtain sample 13 with a lubricating layer formed on the tube substrate.
[0165] Comparative Example 4 After adding 0.5g of copolymer 14 to 12.3g of acetone, 6.18g of 0.30% sodium bicarbonate aqueous solution was added and stirred for 1 hour to obtain coating solution 14.
[0166] Instead of coating liquid 1 in Example 1, the above-mentioned coating liquid 14 was used. Otherwise, the same procedure as in Example 1 was followed to obtain sample 14 with a lubricating layer formed on the tube substrate.
[0167] For samples 1 to 14 obtained above, lubricity and sliding durability (lubrication maintenance) were evaluated according to the following method. The results are shown in Table 1 below. It should be noted that, regarding copolymer 15 of synthetic example 15, since copolymer 15 could not be obtained by synthesis, a sample could not be prepared.
[0168] Table 1 below shows the ratios of N,N-dimethylacrylamide (structural unit (A-1)), acrylic acid (salt) (structural unit (A-2)), and glycidyl methacrylate (structural unit (B)) in each copolymer (“DMAA:AA:GMA (molar ratio)” in Table 1 below), the ratio of the total composition of N,N-dimethylacrylamide and acrylic acid (salt) to glycidyl methacrylate (“(DMAA+AA):GMA (molar ratio)” in Table 1 below), and the ratio of acrylic acid (salt) relative to the total composition of N,N-dimethylacrylamide and acrylic acid (salt) (“AA / (DMAA+AA (molar %)” in Table 1 below). In Table 1 below, for Comparative Example 5 (polymer 15), since no copolymer was obtained, the charge ratio during polymerization is recorded.
[0169] [Evaluation of Sliding Resistance Value] Using an Oak River sliding tester (manufactured by Oak River Technology A PaR Systems Company, DL1000), the sliding resistance value of the lubricating layer of each sample was determined according to the following steps.
[0170] The container was filled with RO water, and the samples were fixed so that the measurement area was immersed. After immersing the samples for 1 minute, the samples were clamped in using silicone terminals (13mm × 32mm) with a load of 500gf. While applying a clamping force of 500gf to the silicone terminals, the samples were moved at a sliding distance of 50mm and a sliding speed of 20mm / sec, and the same part of the sample was repeatedly slid vertically 20 times. At this time, the sliding resistance value (gf) when the sample was pulled vertically was measured on the 5th, 10th, and 20th times. It should be noted that before measuring the sliding resistance value, a metal core was inserted into the inner cavity of the sample (tube substrate).
[0171] In this evaluation test, from the viewpoint of the lubricity (smoothness) of the lubricating layer, the sliding resistance value at the 20th test is permissible to be 15 gf or less, preferably 14 gf or less, more preferably 10.0 gf or less, and particularly preferably less than 10.0 gf. Furthermore, from the viewpoint of the sliding durability (lubrication maintenance) of the lubricating layer, the difference between the sliding resistance value at the 20th test and the sliding resistance value at the 5th test (= sliding resistance value at the 20th test - sliding resistance value at the 5th test) (“Difference” in Table 1 below) is permissible to be less than 6.0 gf, preferably less than 2.0 gf, more preferably less than 1.0 gf, further preferably less than 0.4 gf, and particularly preferably less than 0.4 gf.
[0172] [Table 1] As shown in Table 1, compared with samples 11-14 of the comparative examples, the sliding resistance values of samples 1-10 of the examples in the 20th evaluation of sliding resistance value were significantly lower, indicating excellent lubricity (smoothness). In particular, the sliding resistance values of samples 2, 4-9 in the 20th evaluation of sliding resistance value were less than 10.0 gf, indicating particularly excellent lubricity (smoothness).
[0173] Furthermore, in the evaluation of sliding resistance values for samples 1-8, the difference between the sliding resistance value at the 20th test and the sliding resistance value at the 5th test was less than 1.0 gf. Compared with samples 9-10, whose difference was greater than 1.0 gf, the sliding durability (lubrication maintenance) was superior. In particular, in the evaluation of sliding resistance values for samples 1, 3-4, and 6-8, the sliding resistance value did not increase between the sliding resistance value at the 5th test and the sliding resistance value at the 20th test, indicating that the sliding durability (lubrication maintenance) was further superior. Based on these results, it can be concluded that by setting the total composition of DMAA and AA (structural unit (A)) relative to 1 mole of GMA (structural unit (B)) to 60 moles or less, and setting the ratio of acrylate (salt) (structural unit (A-2)) in structural unit (A) (AA / (DMAA+AA)) to 6.5 mol% or more and 20.0 mol% or less, lubrication and sliding durability can be further balanced and achieved simultaneously.
[0174] Furthermore, in Sample 1 of Example 1 and Sample 12 of Comparative Example 2, the ratio of structural units derived from hydrophilic monomers (DMAA and AA, or DMAA only) to structural units derived from hydrophobic monomers (GMA) was the same. On the other hand, it was found that compared with Sample 12, the sliding resistance values of Sample 1 in the 5th, 10th, and 20th times of the [evaluation of sliding resistance value] were significantly lower (significantly superior lubricity). This can be attributed to the fact that copolymer 1 further has structural units derived from acrylic acid (salt).
[0175] Furthermore, it can be seen that compared with sample 11 of Comparative Example 1, the sliding resistance values of sample 1 in Example 1 were significantly lower in the 5th, 10th, and 20th times of the [evaluation of sliding resistance value] (significantly superior lubricity). This can be attributed to the fact that the total composition of DMAA and AA (structural unit (A)) in copolymer 1 relative to 1 mole of GMA (structural unit (B)) is more than 10 moles. Therefore, the structural units derived from hydrophilic monomers (DMAA and AA, or DMAA only) account for a large proportion in copolymer 1, thereby exhibiting excellent lubricity.
[0176] In Comparative Example 3, Sample 13 contained 82 moles of structural units derived from hydrophilic monomers (DMAA and AA) relative to 1 mole of structural units derived from hydrophobic monomers (GMA). Therefore, Sample 13 exhibited a sliding resistance value of less than 10 gf in the 5th iteration of the [Sliding Resistance Value Evaluation], indicating excellent lubricity (smoothness). However, Sample 13 also showed a significant increase in sliding resistance value between the 5th and 10th iterations, resulting in low sliding durability (lubrication maintenance). It can be concluded that Sample 13's film strength and sliding durability were not sufficiently improved because the ratio of acrylate (salt) (structural unit (A-2)) in structural unit (A) (AA / (DMAA+AA)) was less than 3 mol%.
[0177] In Comparative Example 4, Sample 14 contained 91 moles of hydrophilic monomers (DMAA and AA) relative to 1 mole of structural units derived from hydrophobic monomers (GMA), representing a very high ratio of hydrophilic monomers (DMAA and AA) to structural units derived from hydrophobic monomers (GMA). Although Sample 14 contained acrylate (salt) (structural unit (A-2)) in structural unit (A) (AA / (DMAA+AA)) of over 3 mol%, the sliding resistance value increased significantly between the 5th and 10th sliding resistance values in the [evaluation of sliding resistance value], resulting in low sliding durability (lubrication maintenance). Therefore, it can be concluded that Sample 14, due to having more than 90 moles of hydrophilic monomers (DMAA and AA) relative to 1 mole of structural units derived from hydrophobic monomers (GMA), failed to sufficiently improve the film strength of the lubricating layer and thus failed to sufficiently enhance its sliding durability.
[0178] Here, compared with sample 13 of Comparative Example 3, the sliding resistance value of sample 10 in [Evaluation of Sliding Resistance Value] of Example 10 and the difference between the sliding resistance value of the 20th time and the sliding resistance value of the 5th time are significantly lower (excellent lubricity and sliding durability). In sample 10, relative to 1 mole of structural unit derived from hydrophobic monomer (GMA), there are 86 moles of structural units derived from hydrophilic monomers (DMAA and AA), and the ratio of acrylate (salt) (structural unit (A-2)) in structural unit (A) (AA / (DMAA+AA)) is 3% or more. Therefore, it can be considered that by setting the structural units derived from hydrophilic monomers (DMAA and AA) to 90 moles or less relative to 1 mole of structural units derived from hydrophobic monomer (GMA), and setting the ratio of acrylate (salt) (structural unit (A-2)) (AA / (DMAA+AA)) in structural unit (A) to 3 mol% or more, the lubricity and sliding durability of the lubricating layer can be improved.
[0179] Furthermore, compared to Sample 12 of Comparative Example 2, Sample 2 of Example 2 showed a significantly lower sliding resistance value in the 20th iteration of the [Evaluation of Sliding Resistance Value] (excellent lubricity). Additionally, the difference between the sliding resistance value of Sample 2 in the 20th iteration and the sliding resistance value in the 5th iteration was small, indicating sufficient sliding durability. In Sample 2, relative to 1 mole of structural unit derived from the hydrophobic monomer (GMA), there were 13 moles of structural units derived from the hydrophilic monomers (DMAA and AA), and the ratio of acrylate (salt) (structural unit (A-2)) in structural unit (A) (AA / (DMAA+AA)) was 30.8 moles. Therefore, in conjunction with the content of Comparative Example 5, it can be considered that in the copolymer, by setting the number of structural units derived from hydrophilic monomers (DMAA and AA) to 90 moles or less relative to 1 mole of structural units derived from hydrophobic monomers (GMA), and by setting the ratio of acrylate (salt) (structural unit (A-2)) in structural unit (A) (AA / (DMAA+AA)) to 40 moles or less, the lubricity and sliding durability of the lubricating layer can be sufficiently improved.
[0180] This application is based on Japanese Patent Application No. 2024-52931, filed on March 28, 2024, the disclosure of which is incorporated herein by reference in its entirety.
Claims
1. A medical device having a substrate layer and a lubricating layer formed on at least a portion of the substrate layer, wherein, The lubricating layer comprises a copolymer having: a structural unit (A) comprising a structural unit (A-1) derived from a hydrophilic monomer having an acrylamide group or a methacrylamide group, and a structural unit (A-2) derived from a hydrophilic monomer having at least one of a carboxyl group and a salt of a carboxyl group; and a structural unit (B) derived from a hydrophobic monomer having an epoxy group. The content of the structural unit (A) is more than 10 moles and less than 90 moles relative to 1 mole of the structural unit (B). The content of the structural unit (A-2) is more than 3 mol% and less than 40 mol% relative to the total amount of the structural unit (A-1) and the structural unit (A-2).
2. The medical device as described in claim 1, wherein, The content of the structural unit (A) is more than 25 moles and less than 70 moles relative to 1 mole of the structural unit (B).
3. The medical device as described in claim 1, wherein, The content of the structural unit (A-2) is more than 6 mol% and less than 30 mol% relative to the total amount of the structural unit (A-1) and the structural unit (A-2).
4. The medical device as described in claim 1, wherein, The structural unit (A-1) is a structural unit derived from at least one monomer selected from the group consisting of acrylamide, N-methylacrylamide, N,N-dimethylacrylamide, N-ethylacrylamide, N,N-diethylacrylamide, N,N-dimethylaminopropylacrylamide, N,N-dimethylaminopropylmethylacrylamide, 2-acrylamido-2-methylpropanesulfonic acid, N-(2-hydroxyethyl)acrylamide, N-(2-hydroxypropyl)acrylamide and N-(2-hydroxybutyl)acrylamide.
5. The medical device as described in claim 1, wherein, The structural unit (A-2) is a structural unit derived from at least one monomer selected from the group consisting of acrylic acid and methacrylic acid, as well as their alkali metal salts, alkaline earth metal salts and quaternary ammonium salts.
6. The medical device as described in claim 1, wherein, The structural unit (B) is a structural unit derived from at least one monomer selected from the group consisting of glycidyl acrylate, glycidyl methacrylate, 3,4-epoxycyclohexyl methyl acrylate, 3,4-epoxycyclohexyl methyl methacrylate, β-methyl glycidyl acrylate and β-methyl glycidyl methacrylate.
7. The medical device as described in claim 1, wherein, The structural unit (A) is formed by randomly arranging the structural units (A-1) and (A-2).
8. The medical device as described in claim 1, wherein, The structural unit (B) is configured in a segmented manner.
9. The medical device as claimed in claim 1, wherein, The structural unit (A) is composed of the structural units (A-1) and (A-2) arranged randomly, and the structural unit (B) is arranged in a segmental manner.
10. The medical device as claimed in claim 1, wherein, The medical device is a catheter, stent, or guidewire.
Citation Information
Patent Citations
Medical tool, with lubricative surface in wet state and manufacture therefor
JP1996033704A
Solid with grafted surface and its production
JP1999263819A
Nano structural functional material
JP2002145971A
Solid lubricating material
JP2006316169A
Nucleic acids for cell recognition and integration
JP2024052931A
